STRATIGRAPHIC ANALYSIS : RAJAMANDALA FORMATION AND CITARUM FORMATION BASED ON OUTCROPS DATA - Gani, Reza Mohamad Ganjar; Firmansyah, Yusi; Pamengkas, Satrio Fajar (Faculty of Geological Engineering, Universitas Padjadjaran, 2020)
The location of study area is in Padalarang, West Java with Rajamandala Formation and Citarum Formation outcrop as observation object. Rajamandala Formation is characterized by shallow marine deposit and carbonate sedimentary rock. Meanwhile, Citarum Formation is identified as deep marine deposit and consists of clastic sedimentary rock. The methods used in this study are fieldwork, laboratory analysis, data interpretation, and stratigraphic analysis. Laboratory analysis consists of petrographic analysis and foraminiferal analysis. The contact between these formations is not identified in study area. Outcrop observation exposes improper data to determine the stratigraphic relation, since covered by debris materials of limestone. Foraminiferal analysis data shows that Rajamandala Formation is formed in Late Oligocene (Lower Te/P20 – P22/N1 – N3) and Citarum Formation is formed in Middle Miocene (N9 – N13). It shows gap of time from N3 until N9. It determines an uncorformity stratigraphic relation between these two formations. The depositional environment changes significantly from shallow marine to deep marine. Study area exposes outcrops data which represent these formations and other additional data needed. It offers a good opportunity to determine the stratigraphic relation between these two formation. Furthermore, it can be used as analogue in determining stratigraphic relation.